(untitled) (Anclajes, 2020)
In the set of recently published novels on the subject of post-dictatorial memory, that of the visual artist Gerber Bicecci (1981) stands out for a writing that uses, among other apparently disparate expressive elements, Venn diagrams, to name the ineffable generated by the disappearance, exile and silence imposed. This paper intends to analyze the writing of Conjunto vacío, highlighting the creative self-reference, and the reading effects based on the coexistence of visual and linguistic codes of different species. According to my interpretation, the novel answers this and other questions that Argentina’s society is still around forty years after the last dictatorship, at which time the crystallized and deceptive responses directed especially to the new generations return.